EXPERT SYSTEM TO DIAGNOSE POLYCYSTIC OVARY SYNDROME (PCOS) USING THE NAÏVE BAYES METHOD - Agustina Simangunsong; Petti Indrayati Sijabat; Evi Ningsih Ana Giawa (Sean Institute, 2022)
The development of information systems and technology including expert systems that use facts, techniques and knowledge and reasoning in solving problems. The expert system that is currently developing is a system that adopts the knowledge of an expert in a particular field. In everyday life, we often encounter problems faced by humans, including disease problems in the human body, so we need to consult an expert in the health sector to solve these problems. However, sometimes patients with disease cannot consult an expert due to the large number of patients as well as time and cost issues. In light of these existing problems, it is necessary to develop a system that can help these patients, namely by developing an Expert System model for diagnosing Polycystic Ovary Syndrome (PCOS) using the Naïve Bayes method. The Naïve Bayes method will assist in diagnosing the disease.